(untitled) (Research, Society and Development, 2021)
Several surveys have been underway around the world in recent months in search of answers about SARS-CoV-2, the cause of the pandemic generated by Covid-19. This is a disease of quick and easy contagion, since the main form of transmission is through direct contact with salivary droplets containing the virus. The appearance of several oral signs in patients affected by Covid-19 has been demonstrated, leading to the theory that viral infection is responsible for the appearance of oral manifestations and other secondary infections by other pathogenic microorganisms. The aim of this study is to condense information about the presence and types of oral manifestations reported in patients with Covid-19. A search was carried out in the PubMed, SciELO, LILACS, Google academic databases using descriptors, strategies and criteria pre-established by two evaluators, independently. The research strategies identified 439 articles. After screening the papers, 426 were excluded and 13 selected to compose this review. It was concluded that it is possible to associate the appearance of oral manifestations with Covid-19. However, there is no evidence that they are changes secondary to treatment or if they are directly related to the coronavirus.